Performance evaluation of different TCP error detection and congestion control strategies over a wireless link. - Lang, Tanja
In this paper we present an evaluation of the two major parts of TCP that impact its performance in wireless environments, namely error detection and congestion control. We have re-implemented the most commonly used TCP error detection and congestion control strategies using a modular design technique. Using this implementation we have evaluated the performance in terms of throughput and underlying network usage of different combinations of these strategies over a lossy link with high propagation delay. Our results have shown that selective acknowledgments work well together with any congestion control mechanism and that some combinations of error detection and congestion control suffer from a high amount of unnecessary retransmissions. Consequentely we prorpose a solution to this proplem.
Keywords: Computer systems organization; Computer communication networks; Network protocols; TCP / IP; Network architecture and design; Wireless Communication; Computing methodologies; Simulation and modeling; Design; Measurement; Performance; Reliability; Standardization; Theory